Study of the Thermal Influence on Retroreflection Coefficient Measurement and Uncertainty Evaluation - Santos, A. J. (2013)
Retroreflection is an optical phenomenon that uses a material designed to direct light back toward the source. Retroreflection is achieved through multiple reflections within a retroreflector material such as microspheres of glass or plastic or prismatic elements. The most common and practical use of retroreflection technology is its application to highway safety. Road signs and pavement markings are two of the most important means of ensuring the safety of drivers. Retroreflectivity, or night time visibility of signs and pavement markings, is essential for efficient traffic flow, driving comfort, and highway safety. The evaluation of photometric characteristics of retroreflector materials in laboratory is, therefore, required in order to assure safety conditions, being the coefficient of retroreflection (RA) the most used measure of the ability of retroreflecting materials to reflect light under the conditions of night time. It specifies, for example, the impression of brightness which the driver of a car receives from an irradiated traffic sign by night. Different methods are used to measure the photometric characteristics of retroreflector materials in laboratory. The evaluation of retroreflectivity can be obtained from experimental measurements of dimensional quantities and luminances (of reference materials and tested materials), being all influenced by thermal effects related to the testing laboratory environment, thus requiring to consider its contribution to the estimates and to the uncertainties of the output quantity (coefficient of retroreflection). Safety requirements related to retroreflective materials are also a concern for market surveillance, translated to lower limits established for the materials characteristic RA provided at international standards and Recommendations (e.g., CIE 198:2011). To evaluate the compliance of materials with the standards a comparison between the class tolerances and the estimates of the coefficient of retroreflection measurement are needed and the conformity assessment should also take into account the combined measurement uncertainty including the contributions of influence quantities, namely, due to laboratory testing indoor temperature. In the present document a study of the influence of ambient temperature on the laboratory measurement of the coefficient of retroreflection is presented. Additionally, uncertainty sources are identified and a method to evaluate measurement uncertainty is presented.